1994
DOI: 10.1037/0022-3514.66.3.474
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy motivation attenuates covert priming: The systematic reprocessing of social information.

Abstract: Three studies tested the hypothesis that assimilation of impressions to primed constructs is a product of relatively superficial processing and is unlikely to occur when behavioral information about a target person is processed systematically. In Study 1, the impressions of accuracy-motivated Ss did not assimilate to covertly primed trait constructs, although the impressions of unmotivated Ss did. Studies 2 and 3 showed that when Ss become accuracy motivated after exposure to target information, both retrieval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
212
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(225 citation statements)
references
References 111 publications
10
212
1
2
Order By: Relevance
“…In fact, some have argued that such recategorization does not occur (Trope & Alfieri, 1997). However, a few researchers recently have found evidence that, with sufficient motivation and cognitive resources, perceivers can effortfully correct their categorizations for biasing influences, at least under certain circumstances (Thompson, Roman, Moskowitz, Chaiken, & Bargh, 1994). For example, Weary et al (1999) recently have demonstrated that perceivers can recategorize behavior if they are aware of a biasing influence on their initial judgments and if they perceive that influence to be illegitimate.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some have argued that such recategorization does not occur (Trope & Alfieri, 1997). However, a few researchers recently have found evidence that, with sufficient motivation and cognitive resources, perceivers can effortfully correct their categorizations for biasing influences, at least under certain circumstances (Thompson, Roman, Moskowitz, Chaiken, & Bargh, 1994). For example, Weary et al (1999) recently have demonstrated that perceivers can recategorize behavior if they are aware of a biasing influence on their initial judgments and if they perceive that influence to be illegitimate.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy concerns may often be dwarfed by interpersonal motives in the nonattitude domains of person perception, stereotyping, and relationships (cf. Sedikides, 1990;Thompson, Roman, Moskowitz, Chaiken, & Bargh, 1994). If this intuition is correct, the present research represents one step toward understanding the more and less effortful cognitive pathways by which social goals determine our impressions and judgments of others, and possibly in turn our feelings and actions toward them.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Immediately prior to reading the case summary, participants in the accuracy goal conditions were given instructions designed to activate accuracy concerns. These instructions were adapted from E. P. Thompson, Roman, Moskowitz, Chaiken, and Bargh (1994) and from . They were as follows:…”
Section: Methodsmentioning
confidence: 99%